PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN PERTUMBUHAN PENJUALAN TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - Afi Pradhana; Taufeni Taufik; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to examine the independent variables consisting of Company Size, Profitability and Sales Growth affect the dependent variable is whether the Debt Policy. The population in this study were 16 food and beverage companies listed in Indonesia Stock Exchange. While the sample in this study was 12 companies. The type of data used are secondary data, the data is a company's financial statements. The method of data analysis used is multiple linear regression analysis SPSS version 17. The results of this study indicate that the size effect on the Company's Debt Policy, while Profitability and Sales Growth Debt Policy does not affect the significance of the size of the Company with a value of 0.023, 0.447 Profitability and Sales Growth 0604. Adjusted R Square value is equal to 0.050, which means the amount of 5% of independent variables in this study were able to influence the dependent variable. While the remaining 95% is explained by other variables such as free cash flow, managerial ownership, earnings volatility, growth companies, institutional ownership, liquidity, dividend policy, and asset structure.Keywords : Firm Size, Profitability, Sales Growth, Debt Policy